A Rare Case Of Retinal Arterial Microaneurysm: Clinical Features And Diagnostic Insights - Yuna, Uray Nabila; Ihsan, Grimaldi; Virgana, Rova; Kartasasmita, Arief S.; Iskandar, Erwin; Widyanatha, Made Indra (Indonesian Journal of Medicine, 2025)
Background: In Retinal Arterial Macroaneurysms (RAM), the central retinal artery suffers from acquired focal hypertension. Clinical manifestations of the disease are diverse and easily misdiagnosed. Several imaging modalities may be used in order to confirm the diagnosis of RAM. This article aims to describe the clinical features and method of diagnosis of an uncommon case of retinal artery microaneurysm. Case report: A 57-year-old woman presented with a progressive loss of vision in her right eye months prior. Visual acuity in the right eye was 0.8 log 13. Upon funduscopic inspection of the right eye, firm exudates with low tortuosity and submacular hemorrhage were observed. The right eye’s OCTA revealed a localized expansion and significant constriction with twisted blood vessels on the reverse side of the deformed vessel, while the OCT of the macula revealed submacular hemorrhage. The patient was diagnosed with ruptured retinal Arterial Macroaneurysm or Macular Telangiectasia Type I and Retinopathy Hypertensive Grade II of both eyes, No Diabetic Retinopathy of both eyes with Diabetes Mellitus and Hypertension. The right eye of the patient received concentrated laser photocoagulation and an intravitreal injection of anti-VEGF. Conclusion: RAM is an acquired vascular disease defined by restricted, fusiform, or saccular dilation in the first three arteries of the main retinal artery. Retinal microaneurysms can be diagnosed with various imaging modalities. Ram may be treated with intravitreal anti-VEGF drugs, combination therapy, or laser photocoagulation.